Analysis of Invesment Opportunity Set, Capital Structure and Sales Growth on Profit Growth - Khoirunnisa Azzahra; Siti Chaerunisa Prastiani (Universitas Pamulang, 2022)
This research is motivated by the importance of profit information for its users, both internal and external parties, making each company trying to increase its profits. However, for certain parties, there are those who do it in an unhealthy way to achieve their individual goals on company profit information. This is what makes the practice of profit manipulation currently happening in several companies with the aim of attracting investors to invest their funds in their companies. This study aims to obtain empirical evidence about the factors that influence earnings growth through the investment opportunity set, capital structure, and sales growth variables. This type of quantitative research uses secondary data taken from the BEI of manufacturing companies in the consumer goods industry for the period 2015 - 2020. The sampling method uses purposive sampling. The methodology used is the Chow test, Hausman test, descriptive statistical test, classical assumption test, and panel data regression analysis test using the Eviews program. The results of this study indicate that the investment opportunity set and structural capital have no effect, while sales growth has an effect on profit growth